In-service Novice EFL Teachers’ Perception on Self-Initiated Professional Development: A Narrative Inquiry - Sekar Ayu Wardhani; Endang Fauziati; Dewi Rochsantiningsih (STAI Hubbulwathan Duri, 2024)
Top-down teacher professional development in Indonesia prevents teachers from choosing and determining programs or activities that suit their interests, goals, and needs; however, some activities can assist teachers in developing it, known as self-initiated professional development (SiPD). SiPD demonstrates that people who take the initiative learn more and better than those who are passively taught with or without the assistance of others. This research investigated novice EFL teachers’ perceptions and the types of SiPD they engaged in. This study employed a narrative inquiry approach using semi-structured interviews as data collection. The study involved three EFL teachers selected through purposive sampling. Thematic analysis was employed to analyze the collected data. The findings of this study are that novice EFL teachers regard and comprehend self-initiated professional development positively as responsible professionals seeking to acquire new skills, knowledge, and pedagogy to better prepare for their profession’s obstacles and improve their student’s performance and achievement. They became proactive learners, taking control of their education and taking the initiative to develop their teaching abilities. Furthermore, self-initiated professional development ensured that EFL teachers were current on the newest teaching trends, techniques, and resources.